Advection-Enhanced Gradient Vector Flow for Active-Contour Image Segmentation (Communications in Computational Physics, 2019)
In this paper, we propose a new gradient vector flow model with advectionenhancement, called advection-enhanced gradient vector flow, for calculating the external force employed in the active-contour image segmentation. The proposed modelis mainly inspired by the functional derivative of an adaptive total variation regularizer whose minimizer is expected to be able to effectively preserve the desired objectboundary. More specifically, by incorporating an additional advection term into theusual gradient vector flow model, the resulting external force can much better help theactive contour to recover missing edges, to converge to a narrow and deep concavity,and to preserve weak edges. Numerical experiments are performed to demonstratethe high performance of the newly proposed model.
Keywords: Image segmentation; active contour; gradient vector flow; external force.